2007
DOI: 10.1021/jp0674874
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Infrared Spectral Signatures of 310- and α-Helical Peptides

Abstract: Two-dimensional infrared (2D IR) spectra of Calpha-alkylated model octapeptides Z-(Aib)8-OtBu, Z-(Aib)5-L-Leu-(Aib)2-OMe, and Z-[L-(alphaMeVal)]8-OtBu have been measured in the amide I region to acquire 2D spectral signatures characteristic of 3(10)- and alpha-helical conformations. Phase-adjusted 2D absorptive spectra recorded with parallel polarizations are dominated by intense diagonal peaks, whereas 2D rephasing spectra obtained at the double-crossed polarization configuration reveal cross-peak patterns th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
137
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(146 citation statements)
references
References 90 publications
8
137
0
1
Order By: Relevance
“…The shift of the intrinsic frequency due to interpeptide hydrogen bonds was modeled according to the method proposed by Ge and co-workers, 62 who found that the shifts of the amide I oscillator frequencies are well described by proportional relations to the Kabsch-Sander bond energies. 63 The electrostatic Kabsch-Sander energy of a hydrogen bond between C=O and NH groups is…”
Section: Amide I Band Calculationmentioning
confidence: 99%
“…The shift of the intrinsic frequency due to interpeptide hydrogen bonds was modeled according to the method proposed by Ge and co-workers, 62 who found that the shifts of the amide I oscillator frequencies are well described by proportional relations to the Kabsch-Sander bond energies. 63 The electrostatic Kabsch-Sander energy of a hydrogen bond between C=O and NH groups is…”
Section: Amide I Band Calculationmentioning
confidence: 99%
“…Thus, transition dipoles are good indicators of peptide secondary structure, for example, since many individual amide I bonds are coupled together in betasheets and α-helices, creating strong transition dipoles. 22,[25][26][27] Of course, one can also detect coupling by the frequency separation, but frequency shifts are not always easily measurable. In the example above, the coupling caused each peak to shift by only 1.5 cm −1 , which may be difficult to experimentally detect considering that the linewidths of most condensed phase vibrational modes are >10 cm −1 .…”
Section: Introductionmentioning
confidence: 99%
“…The amide I mode has been the subject of most studies due to its strong intensity and the strong coupling between different amide I modes, which allow the use of this mode for structural determination. [18][19][20][21][22][23][24] Typically the spectra are obtained in heavy water in order to remove the strong water bend signal that is located in the same spectral region as the amide I band. This also results in the exchange of the acidic proton bound to nitrogen, and the resulting molecule is called NMA-d.…”
Section: Introductionmentioning
confidence: 99%